2020
DOI: 10.1111/jcmm.15679
|View full text |Cite
|
Sign up to set email alerts
|

PDX regulates inflammatory cell infiltration via resident macrophage in LPS‐induced lung injury

Abstract: Inflammatory cell infiltration contributes to the pathogenesis of acute respiratory distress syndrome (ARDS). Protectin DX (PDX), an endogenous lipid mediator, shows anti‐inflammatory and proresolution bioactions. In vivo, the mice were intraperitoneally injected with PDX (0.1 µg/mouse) after intratracheal (1 mg/kg) or intraperitoneal (10 mg/kg) LPS administration. Flow cytometry was used to measure inflammatory cell numbers. Clodronate liposomes were used to deplete resident macrophages. RT‐PCR, and ELISA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…PDX exerts its effects via ALX receptor pathways. [25] , [26] , [27] Thus, our study used the ALX antagonist BOC-2. As expected, the ALX antagonist reversed the PDX induced improvement on COX-2/L-PGDS-PGD 2 expression both in vivo and in vitro , suggesting that PDX up-regulates COX-2/L-PGDS-PGD 2 signaling via the ALX/FPR2 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDX exerts its effects via ALX receptor pathways. [25] , [26] , [27] Thus, our study used the ALX antagonist BOC-2. As expected, the ALX antagonist reversed the PDX induced improvement on COX-2/L-PGDS-PGD 2 expression both in vivo and in vitro , suggesting that PDX up-regulates COX-2/L-PGDS-PGD 2 signaling via the ALX/FPR2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“… [25] PDX regulates inflammatory cell infiltration via resident macrophage in LPS-induced lung injury. [26] Moreover, PDX was shown to alleviate lung injury induced by LPS via inducing primary rat type II alveolar epithelial cells proliferation and inhibiting their apoptosis in vivo and in vitro . [27] …”
Section: Introductionmentioning
confidence: 99%
“…Protectin DX is described as a newly identified SPM ( Sanceau et al, 2019 ). Emerging studies revealed that PDX could facilitate the resolution of inflammation by driving macrophage emigration, phagocytosis, and M2 polarization ( Xia et al, 2017 ; Ye et al, 2020 ). Moreover, PDX has been found to control progressive inflammation by suppressing platelet aggregation and preventing leukocyte infiltration and oxidative stress ( Stein et al, 2016 ; Hwang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the onset of inflammation, neutrophils and macrophages produce a series of SPMs, including lipoxins, resolvins, protectins, and maresins (16). These SPMs inhibit the excessive infiltration of neutrophils and help orchestrate the return to homeostasis (34)(35)(36). Transcriptome profiling in this study suggested that MCTR1 decreased neutrophil infiltration in which the IL-17 signaling pathway involved, and we confirmed that MCTR1 reduced the expression levels of G-CSF and CXCL1 which regulated neutrophil chemotaxis, decreased neutrophil recruitment in LPS-injured heart.…”
Section: Discussionmentioning
confidence: 99%